118 Demographics and Real World Healthcare Cost and Utilization for Patients With Probable Tardive Dyskinesia. (15th June 2018) - Polson, Michael; Yonan, Chuck; Williams, Ted
Abstract: Background: Tardive dyskinesia (TD) is a movement disorder associated with prolonged exposure to antipsychotics. The current study was designed to describe demographics and comorbidities for patients with a dyskinesia diagnosis as probable TD (cohort 1), patients likely to have undiagnosed/uncoded TD (cohort 2), and a control population. Methods: This retrospective study analyzed Medicaid claims data from July 2013-March 2017. For a pool of patients with a history of 3 months or more of taking an antipsychotic, three cohorts were evaluated: cohort 1 (ICD-9/10 codes for dyskinesia); cohort 2 (propensity score matching to cohort 1); and cohort 3 (patients withschizophrenia, major depressive disorder [MDD], and/or bipolar disorder [BD] and history of ≤2 antipsychotic medications). Outcomes included patient characteristics, Charlson Comorbity Index (CCI) and healthcare utilization (pre-and post [12-month] period). Results: Cohort sizes and characteristics were: cohort 1 (n=1, 887; female, 68%; mean age, 42 years; MDD, 17%; BD, 48%); cohort 2 (n=1, 572; female, 58%; mean age, 39 years; MDD, 22%; BD, 48%); cohort 3 (n=25, 949; female, 67%; mean age, 40 years; MDD, 11%; BD, 49%). Cohorts 1 and 2 had higher comorbidity burden than cohort 3 (mean pre-index CCIs: 0.68, 0.79, and 0.47, respectively; p<0.001 for each cohort). After 12 months, mean per member per year healthcare costs were higher in cohort 1 and2 compared to cohort 3 (21, 293, 18, 988, and 11, 522, respectively), as were mean claims per member per year (185, 138, and 109, respectively). Conclusion: In the study population, patients likely suffering from TD, ICD-9/10 code-confirmed or unconfirmed, have a higher overall comorbidity burden and healthcareutilization than those who probably do not have TD. Funding Acknowledgements: This study was funded by Neurocrine Biosciences, Inc.